2000
DOI: 10.1093/humrep/15.9.1947
|View full text |Cite
|
Sign up to set email alerts
|

Day 5 versus day 3 embryo transfer: a controlled randomized trial

Abstract: Blastocyst transfer has been suggested to improve implantation rate without affecting pregnancy rate. The aim of this study was to compare the pregnancy and implantation rates of day 3 and 5 transfers in a prospective randomized manner. Patients with four or more zygotes were randomly allocated on day 1 to either day 3 or 5 transfers. Fertilization was achieved through regular IVF or intracytoplasmic sperm injection. Zygotes were kept in Medicult IVF medium for day 3 transfers and transferred into G1.2 and G2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
99
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(108 citation statements)
references
References 23 publications
6
99
1
2
Order By: Relevance
“…Many reports have emphasized the difficulties of correctly selecting the best embryo on day 2 [13] 27], whereas in selected patients it ranged from 4.5% [28] to 11% [29]. Only two studies reported cancellation rates of blastocyst transfer in patients without TQE on day 3 [21% [17] and 37% [30]]. By contrast, in our study, only 12% transfers were cancelled when no TQE were available on day 2.…”
Section: Discussioncontrasting
confidence: 74%
“…Many reports have emphasized the difficulties of correctly selecting the best embryo on day 2 [13] 27], whereas in selected patients it ranged from 4.5% [28] to 11% [29]. Only two studies reported cancellation rates of blastocyst transfer in patients without TQE on day 3 [21% [17] and 37% [30]]. By contrast, in our study, only 12% transfers were cancelled when no TQE were available on day 2.…”
Section: Discussioncontrasting
confidence: 74%
“…The following subgroup analyses were performed for ongoing pregnancy/live birth: (1) number of embryos transferred (1; 2; > 2 allowed); (2) 38 Coskun (2000) 39 Emiliani (2003) 40 Fernández-Shaw (2015) 49 Hreinsson (2004) 41 Kolibianakis (2004) 43 Papanikolaou (2005) 46 Papanikolaou (2006) 45 Rienzi (2002) 47 Van der Auwera (2002) …”
Section: Other Analysesmentioning
confidence: 99%
“…These were higher than those reported in most blastocyst studies even though only 0.88, 0.80, and 0.61 more embryos were cultured for Groups I, II, and III, respectively, than the number transferred. Pregnancy and implantation rates with blastocyst transfer have ranged from 21 to 77% and 9-62%, respectively (2,5,6,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). With blastocyst transfer, all embryos are retained in culture to ensure at least two high-quality blastocysts are available for transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Culture of embryos to day-5 or day-6 allows the top-quality embryos in a cohort to develop to good quality blastocysts. However, medium-to-poor quality embryos appear to require the in vivo environment for optimal development beyond day 3 (25,26,28). We have noted that medium-to-poor quality day-3 embryos rarely develop to blastocysts in vitro but often result in pregnancy after day-3 transfer with assisted hatching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation